Statistical Thinking of Prospective Teachers Across Gender, GPA, and Educational Field - La Eru Ugi; Anwar; Sardin (Indonesian Journal of Educational Science (IJES), 2026)
Empirical evidence on how demographic and academic characteristics jointly influence prospective teachers' statistical thinking remains limited, particularly in Indonesian teacher education. This study examined differences in statistical thinking based on gender, Grade Point Average (GPA), activity status, and educational field. A quantitative cross-sectional design was employed involving 170 prospective teachers selected through stratified random sampling from a population of 233 students and graduates. Statistical thinking was measured using a modified test and analyzed using the Rasch model and multivariate analysis. The results indicated that statistical thinking remained at a low-to-moderate level, with the lowest performance in describing data (M = 0.39) and data presentation (M = 0.39). Significant differences were found for activity status (p = .023) and educational field (p = .046), but not for gender (p = .390) or GPA (p = .675). This study provides integrated empirical evidence to support the development of context-sensitive statistics curricula and instructional strategies in teacher education.